Laboratory Obese on Beelonse Braula coeca Feeding Behavior On Honeybee Workers Apls mellifera - Agleyo, Hashmi A. (Al-Mukhtar Journal of Sciences, 2007)
The feeding behavior and the path have been taken by video camera on the beelouse Braula coeca. The observation showed that the most common and preferred place for the fly is the thorax especially on the third segment, before it scrambles to the bee's head it lifts front legs and then climbs the bee's head and passes medially the frontal margin of one of the compound eyes and between the antennal bases and it then moves directly to the bee's mouth parts where it inserts its proboscis between the mandibles and starts fe3eding. The fly did not feed directly from honey found in any place except in the host mouth parts.